Discusiones en torno a la presunción de la inocencia en el ámbito jurídico angloamericano - Díaz, Ernesto Matías (Pontificia Universidad Católica del Perú, 2024)
This paper systematizes and compares, based on the reasoning of the U.S. Supreme Court and its decisions, four pairings of concepts that arise from discussions on the operability of the presumption of innocence in the Anglo-American legal system. The article illustrates that the partial conclusions in each of these comparisons must be reached by arguments consistent with the normative foundation of the presumption of innocence principle in order to find the defining characteristics of said principle. Ultimately, the paper sets forth a definition of the presumption of innocence that encompasses each of the partial conclusions thus reached.

El presente artículo sistematiza, a partir de referencias encontradas en la jurisprudencia de la Corte Suprema de Justicia de los Estados Unidos, los enfrentamientos de pares conceptuales surgidos de discusiones sobre la operatividad de la presunción de la inocencia en el ámbito angloamericano. El estudio demuestra que las conclusiones parciales en cada una de esas confrontaciones, como características definitorias del derecho a la presunción de la inocencia, deben ser obtenidas mediante argumentos consistentes con el fundamento normativo de este derecho. Como resultado, el artículo expone una noción de presunción de la inocencia que abarca cada una de las conclusiones parciales alcanzadas de esa manera.
Discussions on the Presumption of Innocence in the Anglo-American Legal System
Keywords: Presumption of innocence; Actual innocence; Legal innocence; Probatory innocence; Standard of proof; Due process; Supreme Court of the United States; Presunción de inocencia; Inocencia fáctica; Inocencia jurídica; Estándar de prueba; Debido proceso; Inocencia probatoria; Corte Suprema de Justicia de los Estados Unidos; https://purl.org/pe-repo/ocde/ford#5.05.01